ไฮโดรจิเนชันของคาร์บอนไดออกไซด์บนตัวเร่งปฏิกิริยา Fe-Co แบบโครงสร้างแกน-เปลือก - ปราณปริยา ไตรโชค (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
CO2 hydrogenation to hydrocarbons is a promising way to solve the energy and environmental issues caused by CO2 emissions. CO2 can be also hydrogenated to hydrocarbons by going through the reverse water gas shift reaction and Fischer-Tropsch synthesis reaction. This research studies core-shell structured Fe-Co catalysts which convert CO2 to hydrocarbons by using two interfaces of a Fe on carbon sphere as a core and Co on SiO2 as a shell. A four steps procedure was designed to produce the core-shell structured Fe-Co catalyst. First, carbon sphere (CS) was prepared by hydrothermal carbonization. The next step was to load Fe onto the pre-synthesized CS by the impregnation method. A sol-gel approach was adopted to coat a mesoporous SiO2 shell on the CS-Fe core. Finally, Co was loaded onto the SiO2 shell. The scanning electron microscopy, transmission electron microscopy with energy dispersive X-ray spectrometry, X-ray diffraction and N2 physisorption analysis confirmed the existence of the silica formation. It indicated that core-shell structured Fe-Co catalysts can be prepared by referring methodology. The CO2 hydrogenation was carried out in a fixed-bed reactor under a temperature of 300 ºC with a pressure of 25 bar and an H2/CO2 ratio of 3. The catalytic performance of the catalyst gave 47.02% CO2 conversion with 87.38% selectivity of methane.